2010
DOI: 10.1097/pts.0b013e3181fca8b4
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Physician Knowledge and Counseling Practices Regarding Acetaminophen

Abstract: Objective: To assess physician knowledge regarding acetaminophen dosing, toxicity, and recognition of acetaminophen-containing products and counseling practices when prescribing acetaminophen-containing medications.Methods: Resident and faculty physicians at 1 internal medicine and 2 family medicine residency programs in Alabama were asked to participate in a voluntary survey. Participants completed a 7-item selfadministered questionnaire. Questions were designed to assess physician knowledge of acetaminophen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…In interpreting our reported rates of exceeding the daily 4‐g limit, it is important to note that they are not general‐population rates: as in our previous analyses , but unlike analyses in other studies , the rates are based on individuals who had used paracetamol in the 30 days preceding the study, and who also used it during the week of diary‐keeping. Thus, the present rates are based on a sample of relatively frequent users of paracetamol, and probably over‐estimate the overall population rates of exceeding 4 or 8 g paracetamol in a day.…”
Section: Discussionmentioning
confidence: 94%
“…In interpreting our reported rates of exceeding the daily 4‐g limit, it is important to note that they are not general‐population rates: as in our previous analyses , but unlike analyses in other studies , the rates are based on individuals who had used paracetamol in the 30 days preceding the study, and who also used it during the week of diary‐keeping. Thus, the present rates are based on a sample of relatively frequent users of paracetamol, and probably over‐estimate the overall population rates of exceeding 4 or 8 g paracetamol in a day.…”
Section: Discussionmentioning
confidence: 94%
“…5056 The variation may be partially explained by different survey formatting 42,43. Our survey only listed options in gram amount and the correct answer (<4 g/day) was the highest of the 5 options provided.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have assessed physician‐counseling practices regarding acetaminophen. One study by Hornsby and colleagues found the majority of physicians (72%) self‐reported providing some counseling when prescribing acetaminophen‐containing medications; however, the information provided to patients was limited [9]. A study by Osborne and Bryant assessed patients' receipt of written emergency department (ED) discharge instructions and found none of the 108 patients receiving opioid‐acetaminophen medications were given written information advising them to discontinue other acetaminophen‐containing medications once they began taking opioid‐acetaminophen medications [10].…”
Section: Introductionmentioning
confidence: 99%